Treatment of Vertebrate Osteomielitis with Candida spp. using Caspofungina. The Presentation of a Case Study and a Bibliographical Review - Francisco Arocha; Fabiola Espinoza; Pastor Lizcano; Katynna Parra; Annelly Bracho (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Introduction: Vertebral osteomyelitis (VO) by non-albicans Candida species is an infrequent type of osteomyelitis, however, its incidence has increased due to the increasing number of immunosuppressed patients and invasive procedures. Candida spp is more frequently resistant to azole antifungal drugs, such as fluconazole, than Candida albicans. Methods: We report one case of a 75-year-old diabetic male, with low back pain radiated to both legs, tenderness, and fever 3 weeks after an epidural anesthesia for prostatectomy. Results: VO diagnosis was supported by lumbosacral magnetic resonance imaging (RMI), which showed osteolitic lesions in the L4-L5 spine and the intervertebral disk. Surgical drainage was performed, with a sample for culture yielding Candida spp. The patient was treated with on I.V fluconazole 400 mg per day. Symptoms persisted 15 days later; the erythrocyte sedimentation rate (ESR) was elevated, the C-reactive protein was positive and there was purulent secretion in the surgical wound. A new lumbosacral spine MRI still showed vertebral osteomyelitis and a paravertebral abscess. The patient underwent a new surgical debridement and the sample for culture yielded a heavy growth of Candida spp. In view of the clinical and microbiologic treatment failure, the patient was placed on iv caspofungin 50 mg daily. The patient became asymptomatic after 10 days of treatment; the ESR decreased to 5 mm and the C-reactive protein was negative; therefore, treatment was switched to 200 mg of itraconazole for 3 months. A follow-up MRI showed a L4-L5 spine fusion with no evidence of osteomyelitis. Conclusions: Few cases of epidural blockage related to vertebral osteomyelitis was found in the reviewed literature and this is the only case due to Candida. The percentage of fluconazole-resistant C. tropicalis isolates is low but when no-albicans Candida fluconazole resistance emerges, alternatives such as amphotericin B and caspofungin have to be used. Caspofungin was chosen in this case due to the patient